2008
DOI: 10.1901/jeab.2008.90-345
|View full text |Cite
|
Sign up to set email alerts
|

Interresponse Time Structures in Variable‐ratio and Variable‐interval Schedules

Abstract: The interresponse-time structures of pigeon key pecking were examined under variable-ratio, variableinterval, and variable-interval plus linear feedback schedules. Whereas the variable-ratio and variableinterval plus linear feedback schedules generally resulted in a distinct group of short interresponse times and a broad distribution of longer interresponse times, the variable-interval schedules generally showed a much more continuous distribution of interresponse times. The results were taken to indicate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
50
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(59 citation statements)
references
References 23 publications
8
50
1
Order By: Relevance
“…As a consequence, rate emission may lower more, leading to still longer IRIs. Indeed, Bowers, Hill, and Palya (2008) recently reported such behavior patterns on a VI schedule.…”
Section: Discussionmentioning
confidence: 89%
“…As a consequence, rate emission may lower more, leading to still longer IRIs. Indeed, Bowers, Hill, and Palya (2008) recently reported such behavior patterns on a VI schedule.…”
Section: Discussionmentioning
confidence: 89%
“…Such patterns have been evident with key-poking and lever-pressing by rats, as described above, and with nose-poking by mice (Johnson et al, 2009(Johnson et al, , 2011. But attempts to find evidence of broken-stick log survivor plots with key pecking by pigeons have largely failed (Bennett, Hughes, & Pitts, 2007;Bowers et al, 2008). In at least one case (Bowers et al) a likely source of the problem is that virtually all the IRTs were shorter than 5 s whereas with rats and mice, a substantial proportion of the distribution-mostly in the right tail-has usually extended beyond 30 s (and sometimes beyond 200 s).…”
Section: Conceptual Integration Of Different Performancesmentioning
confidence: 89%
“…This kind of plot shows the proportion of IRTs in a sample that are longer than any particular duration, t. For a wide range of species and activities, log survivor plots of response times often have an odd shape that has been described as looking like a "broken stick" (Clifton, 1987;Fagen & Young, 1978;Johnson, Bailey, & Newland, 2011;Langston, Collett, & Silby, 1995;Machlis, 1977;Slater, 1974;Staddon & Zanutto, 1997; for some exceptions see Bowers, Hill, & Palya, 2008;Tolkamp & Kyriazakis, 1999). The top panel in Figure 5 shows an idealized (although not unrealistic) example of a broken-stick log survivor plot.…”
Section: Bouts Of Responding From Variableinterval Schedulesmentioning
confidence: 99%
“…There is some debate as to whether this assumption is true. For example, Shull (2004) has shown that behavior often seems discontinuous, alternating between periods of action and inaction, while Bowers et al (2008) have argued that response emission on some schedules seems well characterized by assuming that emission is continuous. Evaluation of the integrity of the copyist model's assumption that response emission is continuous awaits further work.…”
Section: Limitations Of the Copyist Modelmentioning
confidence: 99%
“…The finding of a rate difference between VR and VI schedules that provide the same rate of reinforcement has generated considerable interest among operant-oriented researchers (Baum, 1973(Baum, , 1981(Baum, , 1993Bowers, Hill, & Palya, 2008;Catania et al, 1977;Cole, 1994Cole, , 1999Dawson & Dickinson, 1990;Ferster & Skinner, 1957;Morse, 1966;Peele et al, 1984;Reed, Hildebrandt, DeJongh, & Soh, 2003;Reed, Soh, Hildebrandt, DeJongh, & Shek, 2000). Empirical and theoretical reasons drive this interest.…”
mentioning
confidence: 99%